2019
DOI: 10.1088/2057-1976/ab3330
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis on imaging the calcaneus using microwaves

Abstract: The bone quality is asociated with changes in its dielectric properties (permittivity and conductivity). The feasibility of detecting changes in these properties is evaluated using a tomographic array of 16 monopole antennas with z-polarized microwaves at 1.3GHz. The direct problem was evaluated computationally with the Finite-Difference-Time-Domain (FDTD) method. Local and global sensitivity analysis were considered for identifiyng the parameters that most affect the detection. We ob-1 arXiv:1709.04934v1 [phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…The geometry of each model considers the whole heel as a two dielectric media: (I) surrounding tissue (muscle/tendon), and (II) calcaneus (considered as trabecular bone). This simplified model is based on the results presented in the sensitivity analysis of our previous work [10]. The range of values of conductivity and permittivity of the materials employed in computer model are shown in Table 1 [10].…”
Section: Electromagnetic Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometry of each model considers the whole heel as a two dielectric media: (I) surrounding tissue (muscle/tendon), and (II) calcaneus (considered as trabecular bone). This simplified model is based on the results presented in the sensitivity analysis of our previous work [10]. The range of values of conductivity and permittivity of the materials employed in computer model are shown in Table 1 [10].…”
Section: Electromagnetic Simulationsmentioning
confidence: 99%
“…In the simulations we computed the absolute value of the total field (|E z |) in the receiver antennas (Rx). This magnitude was measured in the seven receiver antennas right in front of the transmitter (Tx), since in [10] was shown that these antennas have considerably more information than the others. A complete simulation gives a total of 7×16 = 112 measurement points.…”
Section: Electromagnetic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current state-of-art in using MWT for bone imaging focuses on extracting the electrical properties of the calcaneus, which is also called the heel bone [6,[21][22][23]. In this paper, microwave imaging is performed across the lower midsection of the leg to estimate the electrical properties of the tibia and/or fibula bones; the tibia is the bigger bone located in the shaft of the lower leg, while the fibula is the smaller bone.…”
Section: Introductionmentioning
confidence: 99%
“…La definición del primero fue inspirado en [100] y el segundo se basó en el Método de Morris [101] (ver Apéndice C). Estos métodos se evaluaron en los parámetros de dispersión (parámetros S) sólo para el módulo del campo eléctrico, aunque también realizamos la evaluación del comportamiento de la fase en [102].…”
Section: Análisis De Sensibilidad Aplicación a La Tmo En El Calcáneounclassified